Responsibility Analysis of Land Deed Officials in the Transfer of Disputed Land Rights Implementation - Dhian Ekasari; Bambang Tri Bawono (Sultan Agung Notary Law Review, 2021)
The purpose of this research is to find out and analyze: 1). PPAT's responsibility in the transfer of land rights. 2). Implementation of the Registration of Transfer of Land Rights by Sale and Purchase in Magetan Regency. 3). Legal consequences for Land Deed Making Officials (PPAT) who make disputed land deeds in Magetan Regency. This research is a normative juridical approach, with a sociological juridical approach. The collection of primary and secondary data was obtained by using interview techniques and literature study, then analyzed by using qualitative analysis methods. The results of the research concluded: 1) The responsibility of the Land Deed Making Official (PPAT) in the transfer of land rights is regulated in Article 55 of the Regulation of the Head of BPN No. 1 of 2006, PPAT is personally responsible for the implementation of his duties and positions in every deed making. Civilly, the PPAT is responsible individually or personally for his actions in the implementation of his position, both for the deed he made. 2). The implementation of the registration of the transfer of land rights by sale and purchase in Magetan Regency begins with the stage of implementing a sale and purchase transaction between the seller and the buyer. After that, the sale and purchase transaction must be made by the PPAT. PPAT will check the Deposit Receipts (STTS) and PBB Tax Returns (SPPT), then by PPAT the files are brought to the Land Office to be registered as a certificate of ownership for the new land rights holder. After the registration process, the next step is to wait for data verification from the Land Office for the issuance of certificates. 3). The legal consequences of Land Deed Making Officials (PPAT) who make disputed land deeds in Magetan Regency, namely the registration of the transfer of land rights which are the object of dispute related to the recording in the land book is a refusal to register land rights by the local land office so that it cannot registration or amendment of land data is carried out during the blocking. Based on Article 45 PP No. 24 of 1997, the land office refused to register by returning the file in the form of a deed, certificates and related documents to the PPAT concerned as the executor of the registration of the transfer of land rights. The legal consequence of the returned sale and purchase deed remains an authentic deed and can be used again as a basis for registration if the blocking has been revoked by the applicant.